14.5k views
4 votes
Simplify -2[9-(x+7)]

User Bublik
by
5.0k points

2 Answers

3 votes

Answer:

Simplify the expression.

2 x − 4

User Philip Dreyer
by
4.9k points
1 vote


\bold{-2[9-(x+7)] = -4+2x}

Solution:

Given, -2[9-(x+7)]

According to the BODMAS rule,

Multiplying the sign inside the brackets we get,


\Rightarrow -2[9-x-7]

On subtracting 9 from 7 we get,


\Rightarrow -2[2-x]

On multiplying (-2) inside the brackets,


\Rightarrow -2*2-(-2* x) (distributive property)


\Rightarrow (-4+2* x)


\Rightarrow (-4+2x)

User Oliver Bock
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.